Breaking the Barriers: Erosion of Living Values in Intergenerational Contexts - Bhattarai, Tikaram (GS WOW: Wisdom of Worthy Research Journal, 2024)
This study explores the erosion of respect and collaboration within extended families, focusing on the intergenerational relationships between adults, youth, and the elderly. Using narrative inquiry and a qualitative research design, the research investigates how these core values are diminishing over time due to unmet societal expectations, cultural shifts, and technological advancements. The theoretical framework integrates Maslow’s Need Theory, Durkheim’s Social Integration Theory, and Hybridization Theory to provide insights into the evolving dynamics of values in relation to social needs, collective awareness, and cultural exchange. Data were collected through in-depth interviews and on-site observations of six extended families in Bardibas, Mahottari. The findings reveal a shift from group satisfaction to individualism in cooperation, while respect is transitioning from traditional religious practices to more secular forms. These changes reflect a broader cultural shift, where conventional norms are being redefined to accommodate modern circumstances. The study underscores the importance of understanding the factors driving value erosion and highlights the need for adaptive strategies to preserve essential societal values.